Al-Risāla (attributed to al-Šāfiʿī) and the Question of Vagueness in Islamic Legal Hermeneutics. (12th August 2017) - Belhaj, Abdessamad
Abstract : This article investigates the problem of legal vagueness in Islamic legal hermeneutics. In particular, it examines al-Risāla's (attributed to al-Šāfiʿī) approach to use language as an argument for the clarity of legal discourse. It argues that ambiguity, although recognized as a legal hermeneutic problem, was not tolerated within Islamic legal discourse. It also makes the case that al-Risāla's stance develops early reverse pragmatics or pragmatics-for-apologetics in Islamic legal theory.